Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) x^4 + 2^3-x -2
=x^4 - x^3 + 3x^3 - 3x^2 + 3x^2 - 3x + 2x-2
=x^3.(x-1) + 3x^2.(x-1) + 3x.(x-1)+2.(x-1)
=(x-1).( x^3+ 3x^2 + 3x+2)
=(X+1).(X^3 + 2X^2 + X^2 +2X +X+2)
=(X+1).(X+2).(X^2 +X + 1)
câu c nè
\(\frac{x^2-3x+5}{x+1}=\frac{\left(x^2+2x+1\right)-5x+4}{x+1}=\frac{\left(x+1\right)^2-5\left(x+1\right)+9}{x+1}\)
Ta có \(\frac{x+2}{x+1}=\frac{\left(x+1\right)+1}{x+1}=1+\frac{1}{x+1}\)
\(\frac{x+2}{x+1}=\frac{x}{x+1}+\frac{2}{x+1}\)
\(\frac{2x-3}{x-1}=\frac{2x}{x-1}+\frac{-3}{x-1}\)
\(\frac{x^2-3x+5}{x+1}=\frac{x^2}{x+1}+\frac{-3x+5}{x+1}\)
\(f\left(x\right)=3x^3-7x^2+4x-4=3x^3-6x^2-x^2+2x+2x-4=3x^2\left(x-2\right)-x\left(x-2\right)+2\left(x-2\right)=\left(x-2\right)\left(3x^2-x+2\right)\)
Vì \(f\left(x\right)\) chứa đa thức \(x-2\) nên \(f\left(x\right)\) chia hết cho \(x-2\) (đpcm)